[68Ga]Ga-DOTA-Siglec-9 Detects Pharmacodynamic Changes of FAP-Targeted IL2 Variant Immunotherapy in B16-FAP Melanoma Mice - Viitanen, Riikka; Virtanen, Helena; Liljenbäck, Heidi; Moisio, Olli; Li, Xiang-Guo; Nicolini, Valeria; Richard, Marine; Klein, Christian; Nayak, Tapan; Jalkanen, Sirpa; Roivainen, Anne (Frontiers in Immunology, 2022)
Vascular adhesion protein-1 (VAP-1) is an inflammation-inducible adhesion molecule, which supports contact between leukocytes and inflamed endothelium. There is evidence that VAP-1 is involved in the recruitment of leukocytes to melanoma tumors. Interleukin-2 (IL-2)-based immunotherapy is an efficient therapy that promotes immune system activity against cancers but is associated with toxicity. In the present study, we evaluated the feasibility of PET/CT imaging using the radiotracer [68Ga]Ga-DOTA-Siglec-9, which is targeted to VAP-1, to monitor pharmacodynamic effects of a novel FAP-IL2v immunocytokine (a genetically engineered variant of IL-2 fused with fibroblast activation protein) in the B16-FAP melanoma model. At 9 days after the inoculation of B16-FAP melanoma cells, mice were studied with [68Ga]Ga-DOTA-Siglec-9 PET/CT as a baseline measurement. Immediately after baseline imaging, mice were treated with FAP-IL2v or vehicle, and treatment was repeated 3 days later. Subsequent PET/CT imaging was performed 3, 5, and 7 days after baseline imaging. In addition to in vivo PET imaging, ex vivo autoradiography, histology, and immunofluorescence staining were performed on excised tumors. B16-FAP tumors were clearly detected with [68Ga]Ga-DOTA-Siglec-9 PET/CT during the follow-up period, without differences in tumor volume between FAP-IL2v-treated and vehicle-treated groups. Tumor-to-muscle uptake of [68Ga]Ga-DOTA-Siglec-9 was significantly higher in the FAP-IL2v-treated group than in the vehicle-treated group 7 days after baseline imaging, and this was confirmed by tumor autoradiography analysis. FAP-IL2v treatment did not affect VAP-1 expression on the tumor vasculature. However, FAP-IL2v treatment increased the number of CD8+ T cells and natural killer cells in tumors. The present study showed that [68Ga]Ga-DOTA-Siglec-9 can detect B16-FAP tumors and allows monitoring of FAP-IL2v treatment.